T cell toxicity of HIV latency reversing agents. (January 2019) - Zhao, Manzhi; De Crignis, Elisa; Rokx, Casper; Verbon, Annelies; van Gelder, Teun; Mahmoudi, Tokameh; Katsikis, Peter D.; Mueller, Yvonne M.
Graphical abstract: Abstract: Combination antiretroviral therapy reduces morbidity and mortality in HIV infected patients. However, the cure of HIV infection is hindered by the persistence of the latent HIV reservoir. Latency reversing agents (LRAs) are developed to target the HIV latently infected cells for HIV reactivation. In addition to reversal of HIV latency, the eradication of HIV latently infected cells will require effector HIV-specific CD8+ T cells. Therefore it is imperative we understand how LRAs affect immune cells. We have performed a comparative in depth analysis of the cytotoxicity of several compounds belonging to four LRA classes on T cells, B cells, and NK cells. In addition, the effect of these LRAs on activation and inhibitory receptor expression of CD8+ T cells was examined. We show that the HDAC inhibitors romidepsin and panobinostat are highly cytotoxic for CD4+ and CD8+ T cells, whereas the PKC agonists bryostatin and prostratin and BET inhibitors JQ1 and OXT-015 were less cytotoxic. The BAF inhibitors CAPE and pyrimethamine exhibit no cytotoxicity. Drug-specific cytotoxicity on CD8+ T cells was comparable between healthy controls and cART-treated HIV-infected patients. Bryostatin and both BET inhibitors downregulated the expression of CD279 on CD8+ T cells without affecting their activation. Our comparison of LRAs identified differences in cytotoxicity between LRA classes and members within a class and suggests that some LRAs such as bryostatin and BET inhibitors may also downregulate inhibitory receptors on activated HIV-specific CD8+ T cells. These findings may guide the use of LRAs that have the capacity to preserve or restore CD8+ T cell immunity.